Grounding cognition : the role of perception and action in memory, language, and thinking - Pecher, Diane, 1966-; Zwaan, Rolf A., 1962- (Cambridge University Press, 2005)
One of the key questions in cognitive psychology is how people represent knowledge about concepts such as football or love. Recently some researchers have proposed that concepts are represented in human memory by the sensorimotor systems that underlie interaction with the outside world. These theories represent a recent development in cognitive science to view cognition no longer in terms of abstract information processing, but in terms of perception and action. In other words, cognition is grounded in embodied experiences. Studies show that sensory perception and motor actions support understanding of words and object concepts. Moreover, even understanding of abstract and emotion concepts can be shown to rely on more concrete, embodied experiences. Finally, language itself can be shown to be grounded in sensorimotor processes. This book brings together theoretical arguments and empirical evidence from several key researchers in this field to support this framework.